Multivariate analysis of selected honeybee populations in Africa - Radloff, Sarah E (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1996)
Morphometric characters and sting pheromones of worker honeybees, Apis mellifera Linnaeus were analysed by multivariate methods to characterise selected honeybee populations along five transects in Africa at a meso-scale level of sampling distance resolution. In some, but not all, areas pheromonal clusters were found to be coincident and concordant with the morphometric clusters, thus indicating that different honeybee traits have dispersed variably among populations. All transects were found to contain areas of significantly high variance. High intracolonial variance was taken to indicate localised genetic variation coupled with out-cross matings. Centroids of high intercolonial variance occured at and between cluster boundaries and were typical of transitions between, and rainfall-temperature discontinuities within, ecological-climatological zones, hence areas of ecological instability. Principal component and stepwise discriminant analysis yielded three morphometric clusters corresponding to A. m. sahariensis and A. m. intermissa in Morocco and to A. m. iberica (with three biometric populations) in Spain, but no pheromone clusters. The combined morphometric and pheromonal variance spectra indicated regions of natural hybridisation along a Sahara-Pyrenees transect. In the Horn of Africa, discrete and statistically homogeneous populations were identified: A. m. jemenitica, A. m. bandasii, A. m. sudanensis in Ethiopia and an unclassified group in southwestern Somalia. Areas of high intercolonial variance were interpreted as zones of hybridisation between the populations. Along a transect in west central Africa, three distinct homogeneous populations and two zones of hybridisation were found. These bees were designated as A. m. adansonii whose area of distribution was intruded by an un-named mountain group of bees and a third group, A. m. jemenitica. The delineation of the hybrid zones was supported by intercolonial variance spectra and these significant asymmetries were found to be coincident with transitions between the ecological-climatological zones. In southwestern Africa, two discrete homogeneous populations and a zone of hybridisation between them were identified: A. m. scutellata in northern South Africa and southern Namibia and A. m. adansonii in northern Namibia. Along a transect in the southeastern woodland savanna of Africa, three discrete populations were classified: A. m. litorea in Mozambique, A. m. scutellata in Zimbabwe and A. m. adansonii in northwestern Zambia. A zone of introgression between the last two subspecies occured in south-central Zambia and in the Zambezi valley.
Keywords: Bees -- Africa; Bees